Świętosław Orzelski – a 16th-century parliamentary activist, orator and historian - Kaczorowski, Włodzimierz (The Opole Studies in Administration and Law, 2019)
Świętosław Orzelski (1549–1598), Starost of Radziejów, actively participated in the political life of the noblemen’s Republic of Poland as a parliamentary activist and Member of Parliament. As a deputy he participated in 13 sessions of Parliament, including 6 sessions during the rule of Stefan Batory and 7 ones in the reign of Sigismund III Vasa. He was a talented politician, continuing the best traditions of the execution faction. As one of the seniors of the Augsburg denomination, he belonged to the group of leaders in the fight for religious tolerance. His historical work under the title Acta interregni post obitum nimirum Sigismundi Augusti remained in the form of manuscript for many years. It was not published in the Polish translation until the 19th century by Włodzimierz Spasowicz, and in its original form by Edward Kuntze in 1917. At present, a new edition of the work by Świętosław Orzelski is being prepared. In the first place, an introductory volume will be published, containing Orzelski’s biography, his speeches and letters dedicated to public matters.